Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/17461391.2021.1891296
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and sensitivity of the Notio Konect to quantify coefficient of drag area in elite track cyclists

Abstract: Elite level cycling events are performed at speeds in excess of 50 km/h. At these speeds, over 90% of the resistance forces come from aerodynamic resistance (C D A). Recently bicycle-mounted pitot tubes, such as the Notio Konect (NK) have become more commercially available making C D A easier to measure. Its reliability and sensitivity would be useful for riders and coaches to be able to understand what constitutes as a change in C D A. Accordingly, the aim of this study was to establish the intra-and inter-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
1
6
1
Order By: Relevance
“…13 A subsequent study has confirmed the reliability of the Notio in an indoor velodrome and has shown that this technology can detect small changes in C d A (1.2%). 14 In addition, the C d A calculated during field tests on a straight and flat road of 400 m with the mathematical model integrating meteorological data of a Velocomp Aeropod would be consistent with the values from wind tunnel testing. 5 However, none of these studies tested the validity of this type of device under real and uncontrolled conditions when the cyclist must face the force of the wind and ride at different speeds on varied courses made up of turns, climbs and descents.…”
Section: Introductionsupporting
confidence: 66%
“…13 A subsequent study has confirmed the reliability of the Notio in an indoor velodrome and has shown that this technology can detect small changes in C d A (1.2%). 14 In addition, the C d A calculated during field tests on a straight and flat road of 400 m with the mathematical model integrating meteorological data of a Velocomp Aeropod would be consistent with the values from wind tunnel testing. 5 However, none of these studies tested the validity of this type of device under real and uncontrolled conditions when the cyclist must face the force of the wind and ride at different speeds on varied courses made up of turns, climbs and descents.…”
Section: Introductionsupporting
confidence: 66%
“…The purpose of this study was to evaluate the validity and sensitivity to changes in cyclist position with respect to the measured CdA between the Notio Aerostick device (Kordi et al, 2021;Valenzuela et al, 2020 ¶ ) and two other mathematical models, VE (Dyer & Disley, 2018) and Martin (Martin et al, 2006). Our main finding is that, although the level of agreement of Notio Aerostick with both formulas is satisfactory (ICC>80%), with low and non-systematic error bias, and the differences in CdA are not significant in any of the positions, our results show that Notio Aerostick gives slightly lower values than those obtained by the formulas.…”
Section: Discussionmentioning
confidence: 99%
“…These include mathematical models, such as Virtual Elevation (VE) (Dyer & Disley, 2018) and the Martin's Model (Martin et al, 2006), but also aerosticks devices such as the Notio Aerostick (Argon 18; Montreal, Canada), Aero-Lab.tech (Strathcona Calgary, Canada), and Velocomp LLC (Stuart, Florida, EE.UU). The main feature of this devices is that it includes a pressure sensor capable of measuring wind speed, which together with other external sensors resolve an energy balance equation to obtain a composite value that includes the aerodynamic drag coefficient multiplied by the frontal area; that is, the so called coefficient of aerodynamic drag (CdA) (Kordi et al, 2021;Valenzuela et al, 2020 ¶ ). In the case of aerostick Notio Aerostick, it uses its own equation that has not been published.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations